2016
DOI: 10.3233/jad-150883
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics

Abstract: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The CSF samples were analyzed by ELISA assays for Aβ 1–42 (IBL International 207 GmbH, Hamburg, Germany, Fujirebio Europe, formely Innogenetics, Ghent, Belgium), phosphorylated tau 181 (p‐ tau ) and total tau ( tau ) (Fujirebio 211 Europe) according to the instruction of the manufacturers and a standardized protocol developed by the BIOMARKAPD consortium (Lelental et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The CSF samples were analyzed by ELISA assays for Aβ 1–42 (IBL International 207 GmbH, Hamburg, Germany, Fujirebio Europe, formely Innogenetics, Ghent, Belgium), phosphorylated tau 181 (p‐ tau ) and total tau ( tau ) (Fujirebio 211 Europe) according to the instruction of the manufacturers and a standardized protocol developed by the BIOMARKAPD consortium (Lelental et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements on samples left at RT for longer than 24 hours have been more variable, with studies reporting increasing [100,129] or decreasing [130] CSF Aβ(1-42) concentration, or no effect [131][132][133]. Hypotheses for the increase or decrease include Aβ(1-42) release from amyloid-binding proteins [100], increased Aβ adsorption to tube material [83], or proteolytic degradation [129].…”
Section: Temperature Between Collection and Analysis/storagementioning
confidence: 99%
“…Investigations have consistently shown that CSF biomarkers (Aβ(1-42), pTau and tTau) are reasonably stable over time, when stored at -80°C (Table 3; [ 73,123,130,131,133,134,[137][138][139][140]); a recent study found that, if using a single batch of assays following varying sample storage times, storage for up to 12 years had no significant effect [140]. Only one report was found in this review that deviated from this, describing an increase in concentration of some samples following 7 months [138].…”
Section: Storage Durationmentioning
confidence: 99%
“…For example, Bjerke et al [17] reported that only native CSF without additives is commutable for multiple method comparisons, including mass spectrometry. In addition, the selection of the matrix type for use as a quality control sample in the assay is important [18], while the effect of changes in biomarker concentrations on clinical decision-making must be documented for each analyte [19]. If needed, statistical approaches are available for harmonization of results between study designs or between sample processing procedures [20].…”
Section: Discussionmentioning
confidence: 99%